Should free deep inferior epigastric artery perforator flaps be considered a quality indicator in breast reconstruction?. Issue 12 (December 2019) - Tevlin, Ruth; Wan, Derrick C.; Momeni, Arash
Summary: Over the past several decades, technical advances in breast reconstruction have resulted in the development of flaps that are aimed at progressively decreasing abdominal wall morbidity. There is, however, ongoing controversy related to the superiority of deep inferior epigastric perforator (DIEP) flaps over muscle-sparing TRAM (MS-TRAM) flaps. Hence, the question remains unanswered as to which approach should be considered the standard of care, and more importantly, whether the rate of DIEP flap utilization should be considered a quality metric in breast reconstruction. In this review article, we examine the literature pertaining to abdominal free tissue transfer in breast reconstruction from both donor site and flap characteristics as well as the resultant complications and morbidity. The impact on the donor site remains a prevailing principle for autologous breast reconstruction; thus, must be adequately respected when classifying what is left behind following flap harvest. The most commonly used nomenclature is too simplistic. This, in turn, leads to inadequate incorporation of critical variables, such as degree of muscular preservation, fascial involvement, mesh implantation, and segmental nerve anatomy. Currently, there is insufficient evidence to support DIEP flap harvest as a quality indicator in breast reconstruction, as DIEP flap outcomes are not clearly superior when compared with MS-TRAM flaps.